Dynamic tracking of pathogenic receptor expression of live cells using pyrenyl glycoanthraquinone-decorated graphene electrodes1. Issue 3 (16th March 2015) - He, Xiao-Peng; Zhu, Bi-Wen; Zang, Yi; Li, Jia; Chen, Guo-Rong; Tian, He; Long, Yi-Tao
<x xml:space="preserve">Abstract</x> Dynamic tracking of pathogenic receptor expression with live cells is made possible by pyrenyl glycoanthraquinones decorated on graphene electrodes.